Analysis of the factors that attract customers to invest through Fixed Deposit Receipt / Mudaraba Term Deposit in Trust Bank Limited - Julfiquar, Jakia (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2015.